1995
DOI: 10.1093/ajcp/103.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of Mechanical Disaggregation of Scirrhous Breast Adenocarcinomas for DNA Flow Cytometric Analysis of Whole Cells

Abstract: Mechanical release of single cell suspensions from solid tumors for DNA analysis by flow cytometry has been shown to be optimal for adenocarcinomas in general. In the breast, many adenocarcinomas are fibrotic or scirrhous, creating difficulty in separating the neoplastic cells from the stroma. The authors have conducted a parallel study in 20 consecutive cases of scirrhous adenocarcinomas of the breast using two mechanical methods of cell disaggregation by: (1) mincing tumor tissue in culture media (MINCE); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Large clumps can be removed by nylon mesh filtration (typically 35–53 μm), sheared apart by passage through small gauge needles, or identified on the basis of forward‐angle light scattering (2). Strategies to separate overlapping G 0/1 doublets from the G 2 + M1 population have utilized the gating of correlated measurements of integral DNA fluorescence pulse (≈ area) with either peak pulse height (brightness) (5) or pulse duration (width) (6–9), gating on the G 2 + M cells that lack cyclin B1 protein expression (10), and computer algorithms to model aggregate probability distributions in DNA histograms (4, 11–14).…”
mentioning
confidence: 99%
“…Large clumps can be removed by nylon mesh filtration (typically 35–53 μm), sheared apart by passage through small gauge needles, or identified on the basis of forward‐angle light scattering (2). Strategies to separate overlapping G 0/1 doublets from the G 2 + M1 population have utilized the gating of correlated measurements of integral DNA fluorescence pulse (≈ area) with either peak pulse height (brightness) (5) or pulse duration (width) (6–9), gating on the G 2 + M cells that lack cyclin B1 protein expression (10), and computer algorithms to model aggregate probability distributions in DNA histograms (4, 11–14).…”
mentioning
confidence: 99%
“…These two methods were previously compared for tumor tissue. 33 Torres and colleagues 33 compared dissociation of breast adenocarcinoma with scraping of the tumor and concluded that the methods were comparable.…”
Section: Discussionmentioning
confidence: 99%